2020
DOI: 10.3390/w13010008
|View full text |Cite
|
Sign up to set email alerts
|

Review: Acid Mine Drainage (AMD) in Abandoned Coal Mines of Shanxi, China

Abstract: Excessive exploitation and massive coal mine closures have brought about extensive goafs in Shanxi where 8780 coal mines have been abandoned in the last 20 years. Acid mine drainage (AMD) poses severe environmental impact and has become a prominent problem in Shanxi abandoned coal mine areas, which has aggravated the shortage of water resources and threatened the safety of the local drinking water supply. The purpose of this review is to protect the precious water resources and maintain sustainable use in Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 62 publications
0
23
0
1
Order By: Relevance
“…Acid mine drainage has become a serious global issue in recent times owing to its hazardous impact on the environment and living organisms (Kefeni et al, 2017;Grande et al, 2018;Steyn et al, 2019;Rezaie and Anderson, 2020). In the mining regions of Australia (Lei et al, 2010), Brazil (Galhardi and Bonotto, 2016), Canada (Sracek et al, 2004), England, Wales, Spain, Norway (Hallberg, 2010;Romero et al, 2011), Morocco (Boularbah et al, 2006), South Africa (Ochieng et al, 2010), China (Wu et al, 2009;Wang et al, 2021b), and United States of America (Blowes et al, 2005;Acharya and Kharel, 2020) concern over AMD pollution has been reported, with inactive and abandoned mines generating huge quantities of AMD that contaminates both terrestrial and aquatic systems including agricultural soils, ground-, and surface-water sources (Rezaie and Anderson, 2020). The negative effects of phytotoxicity-related AMD acidity and HM contamination of agricultural soil and crops have been documented (Netto et al, 2013;Liao et al, 2016), the HM entering the food chain through the food crop uptake posing a potential health risk to human population (Kumar et al, 2020;Massányi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Acid mine drainage has become a serious global issue in recent times owing to its hazardous impact on the environment and living organisms (Kefeni et al, 2017;Grande et al, 2018;Steyn et al, 2019;Rezaie and Anderson, 2020). In the mining regions of Australia (Lei et al, 2010), Brazil (Galhardi and Bonotto, 2016), Canada (Sracek et al, 2004), England, Wales, Spain, Norway (Hallberg, 2010;Romero et al, 2011), Morocco (Boularbah et al, 2006), South Africa (Ochieng et al, 2010), China (Wu et al, 2009;Wang et al, 2021b), and United States of America (Blowes et al, 2005;Acharya and Kharel, 2020) concern over AMD pollution has been reported, with inactive and abandoned mines generating huge quantities of AMD that contaminates both terrestrial and aquatic systems including agricultural soils, ground-, and surface-water sources (Rezaie and Anderson, 2020). The negative effects of phytotoxicity-related AMD acidity and HM contamination of agricultural soil and crops have been documented (Netto et al, 2013;Liao et al, 2016), the HM entering the food chain through the food crop uptake posing a potential health risk to human population (Kumar et al, 2020;Massányi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Формирането им се дължи на биологично и химично окисление на сулфидни минерали (пирит, халкопирит, сфалерит, галенит, арсенопирит) при контакт на рудна маса, въглища с високо съдържание на пиритна сяра и минерални отпадъци с въздух и вода (Luther, 1987;Acharya and Kharel, 2020). Протичането на вторични реакции като разтваряне на карбонатни и окисни минерали, неутрализация и йонен обмен води до вариране на състава на КРВ от такива с висока киселинност и съдържание на Fe, Mn, Al, As, цветни метали (Cu, Zn, Cd, Co, Ni) и сулфати до слабо кисели и неутрални води, съдържащи ниски концентрации желязо, наличие на цветни метали и високо сулфатно съдържание (Sheoran and Sheoran, 2006;Brown, 2010;Cravotta, 2010;Wang et al, 2021).…”
Section: въведениеunclassified
“…The mining industry is considered a significant anthropogenic source of water and sediments pollution due to acid mine drainage (AMD) from mine tailings, specifically those of abandoned mines, posing serious environmental hazard to aquatic life [Martinez-Lopez et al, 2021;Alvarenga et al, 2021]. Elevated trace elements concentrations are often found in areas where acid mine waters are discharged from abandoned metal-bearing mines [Wang et al, 2021;Wright et al, 2018]. Trace elements and rare earth elements pollution in the river environment can also have adverse effects on organisms and humans, enter the food chain, and accumulate in aquatic organisms, sometimes at harmful levels [Chan et al, 2021;Byrne et al, 2013;Adeel et al, 2019].…”
Section: Introductionmentioning
confidence: 99%